Human-based adaptive actions in flood disaster risk management: a review of Malaysian case events - Wan Anis Afeeqa Wan Mohammad Azhar,; See Too, Kay Leng; Nurfashareena Muhamad, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Flood occurrences in Malaysia are increasing in both frequency and intensity, highlighting the urgent need for effective Disaster Risk Management (DRM) strategies. This paper explores the critical role of human-based adaptive actions in managing flood risks, emphasizing the importance of local communities, social support networks, and grassroots responses. While top-down approaches led by authorities remain essential, this study shifts focus to bottom-up contributions that enhance overall resilience. Using the PRISMA framework for a systematic review, six relevant articles were selected and analyzed thematically. Key themes identified include social support, collective community engagement, and adaptive actions taken before, during, and after flood events. The findings reveal that community-driven preparedness efforts, psychological support systems, and collaborative emergency responses significantly complement formal DRM mechanisms. These human-centered interventions not only strengthen community resilience but also bridge gaps left by institutional responses. The study advocates for an integrated flood management approach that combines national policies with localized adaptive strategies. Such an approach ensures a more inclusive, responsive, and sustainable framework for flood risk reduction in Malaysia. Strengthening social cohesion, encouraging active participation, and building adaptive capacity are essential steps toward creating safer and more resilient urban and rural settlements in the face of escalating flood risks.